Productive and technological characteristics of guinea pig meat (Cavia porcellus) using diets based on pisonay (Erythrina sp) - Cárdenas Villanueva, Ludwing Ángel (2018)
The objective from work was to evaluate the effect of diets based on Erythrina sp on the productive characteristics of the animal and its carcass. We used 32 male guinea pigs (Cavia porcellus) distributed in 4 treatments that received diets based on Erythrina sp (P) and commercial concentrated (C) feed in the proportions of 100:0% (Control), 75:25% (P75/C25), 50:50% (P50/C50) and 25:75% (P25/C75) respectively. To evaluate the effect of the diets on some productive characteristics and the technological properties of the carcass, was used a completely randomized design with a confidence level of 95%. The differences between averages were determined with Tukey test (P≤0.05). Diets supply to the animals produced variations (P≤0.05) on the increase of live weight and the yield of the carcass. Similarly, variations (P≤0.05) have been found in pH, water retention capacity and carcass coloring rates. The diet P50/C50 based on a mixture of Erythrina sp and commercial concentrate provided a beneficial effect on the productive characteristics without affecting the quality of the meat with respect to the other diets.